Penerapan Algoritma Fuzzy Clustering Untuk Penentuan Jurusan Sekolah Menengah Kejuruan - Basorudin . (RJOCS (Riau Journal of Computer Science), 2015)
Abstract : Fuzzy C-Means algorithm is an algorithm that is easy and is often used in the technique ofgrouping the data as it makes an estimate efsien and does not require a lot of parameters. Severalstudies have concluded that the Fuzzy C-Means algorithm can be used to classify data based oncertain attributes. In this study will be used Fuzzy C-Means algorithm to classify the junior highschool student data based Value core subjects for the majors. The study also examined the level ofaccuracy of Fuzzy C-Means algorithm in determining the majors in Vocational Education. In thispeneitian data to be in Cluster 4 Cluster is comprised of 4 courses in SMK Negeri 1 Rambah namelyComputer Engineering Network